Practice of skin‐to‐skin contact, exclusive breastfeeding and other newborn care interventions in Ethiopia following promotion by facility and community health workers: results from a prospective outcome evaluation. (20th October 2016) - Callaghan‐Koru, Jennifer A.; Estifanos, Abiy Seifu; Sheferaw, Ephrem Daniel; de Graft‐Johnson, Joseph; Rosado, Carina; Patton‐Molitors, Rachel; Worku, Bogale; Rawlins, Barbara; Baqui, Abdullah
Abstract: Aim: To assess the effects of a facility and community newborn intervention package on coverage of early skin‐to‐skin contact (SSC) and exclusive breastfeeding – the therapeutic components of kangaroo mother care. Methods: A multilevel community and facility intervention in Ethiopia trained health workers in 10 health centres and the surrounding communities to promote early SSC and exclusive breastfeeding for all babies born at home or in the facility. Changes in SSC and exclusive breastfeeding were assessed by comparing baseline and endline household surveys. Results: Overall practice of SSC at any time following delivery increased significantly from 13.1 to 44.1% of mothers. Coverage of immediate SSC also increased significantly from 8.4 to 24.1%. Breastfeeding within the first hour increased from 51.4 to 67.9% and exclusive breastfeeding within the first three days increased from 86 to 95.8%. At endline, SSC was significantly higher among facility births than home births and community health workers had limited contact with mothers. Conclusion: While targeted behaviours improved overall, the programme did not achieve adequate increases in SSC and exclusive breastfeeding among home deliveries to expect a reduction in mortality for low birthweight babies. Newborn care programs in Ethiopia should continue to encourage facility delivery while strengthening coverage of community programmes.